(3GdeaUd aj UfYI GdEYQGHs - (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s
(3ChdgG (B:s
(3Gddg CMeO Ydi Cf LYdfj ef YdeGA GdYQHjI dEfTGA cJGH aj GdEYQGH eMjW HcGaI GdCHhGH s
(3BNQgG (B:s
(3hEPG cGfhG eef jMPahf eY EecGf GdEOZGe aj (B"(3jJSY(B" (3h(B"(3jHbi(B" (3age eY YOe EecGfg CMPa Je GdcJGH s
(3GdfSNI HgG MhGTs
(3fSNI QGHYI JJab aj ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa jSjQ LOkG aj HYV GdCdaGXs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs